Manager’s Philosophy And Its Relationship With Career Success - Razak, Azley Abd. (1999)
There are many contributing factors to the career success of managers. This study investigates the effect of manager's philosophy on career success of managers in Malaysia. This study also examined the role of demographic variables and its effect to manager's philosophy (Theory X, Theory Y and Theory Z) and career success. Data were collected by means of questionnaire survey. A total of 112 respondents were sampled for the purpose of this study. Past research had not investigated the contribution of managers philosophy to career success. This study was undertaken to accomplish better understanding of this relationship.